Monoclonal Culture and Characterization of Symbiodiniaceae C1 Strain From the Scleractinian Coral Galaxea fascicularis - Wang, Jun; Chen, Jiaqi; Wang, Shaoyu; Li, Fuyu; Fu, Chengchong; Wang, Yan (Frontiers in Physiology, 2021)
The symbiosis between cnidarian hosts and photosynthetic dinoflagellates of the family Symbiodiniaceae (i.e., zooxanthellae) provides the energy foundation of coral reef ecosystems in oligotrophic waters. The structure of symbiont biota and the dominant species of algal symbiont partly shape the environmental adaptabilityof coral symbiotes. In this study, the algal symbiont cells were isolated from the tentacles of Galaxea fascicularis, a hermatrypic coral with obviousdifferentiation in heat resistance, and were cultured in vitro with an improved L1 medium. An algal monocolonal cell line was established using separated algal culture drops and soft agar plating method, and named by GF19C1 as it was identified as Cladocopium sp. C1 (Symbiodiniaceae) based on its ITS1, ITS2 and the non-coding region of the plastid psbA minicircle (psbAncr) sequences. Most GF19C1 cells were at the coccoid stage of the gymnodinioid, their markedly thickened (ca. two times) cell wall suggests that they developed into vegetative cysts and have sexual and asexual reproductive potential. The average diameter of GF19C1 cells decreased significantly, probably due to the increasing mitotic rate. The chloroplasts volume density of GF19C1 was significantly lower than that of their symbiotic congeners, while the surface area density of thylakoids relative to volumes of chloroplasts was not significantly changed. The volume fraction of vacuoles increased by nearly five-fold, but there was no significant change in mitochondria and accumulation bodies. Light-temperature orthogonal experiments showed that, GF19C1 growth preferred the temperature 25±1℃ (at which it is maintained post-isolation) rather than 28±1℃ under the light intensity of 42±2 or 62±2 μmol photons m−2 s−1, indicating an inertia for temperature adaptation. The optimum salinity for GF19C1 growth ranged between 28-32 ppt，at which the growth rate (K) could increase from 0.024 to 0.108 during 8 to 12 months post-isolation. The monoclonal culture techniques established in this study were critical to clarify the physiological and ecological characteristics of various algal symbiont species, and will be instrumental to further reveal the roles of algal symbionts in the adaptive differentiation of coral-zooxanthellae holobionts in future studies.